China : a new history - Fairbank, John King, 1907-1991.; Goldman, Merle (Cambridge, Mass. : Belknap Press of Harvard University Press, 1998)
Bringing to bear 60 years of research, travel and teaching, John Fairbank's history reaches from China's neolithic days to its troubled present. He depicts a country ever-changing and yet constant in its effort to achieve a cohesive identity, an enormous and enormously complex nation.
Includes bibliographical references and indexes.
Keywords: China -- History